1997
DOI: 10.1093/jac/40.5.729
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial of two antibiotic regimens in the treatment of peritonitis in CAPD patients: teicoplanin plus tobramycin versus cephalothin plus tobramycin

Abstract: A multicentre, comparative, randomized study was performed to compare the efficacy and tolerability of two antibiotic regimens in the treatment of peritonitis in continuous ambulatory peritoneal dialysis (CAPD) patients: teicoplanin plus tobramycin versus cephalothin plus tobramycin. After informed consent had been obtained, 68 patients were randomized prospectively to receive either teicoplanin plus tobramycin or cephalothin plus tobramycin. Patients were followed throughout the study and for up to 4 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
10
2
1
Order By: Relevance
“…This resolution rate was significant higher than initial treatment with a first generation cephalosporin plus aminoglycosides (pooled proportion of 66%, 95% CI 0.57–0.75) from 14 included studies [ 57 , 61 , 64 75 ] with 1,438 total episodes (Figure 3 ). Initial treatment with ceftazidime plus a glycopeptide also showed a higher resolution rate than a glycopeptide plus aminoglycosides (pooled proportion of 75%, 95% CI 0.69–0.80) that were used in 16 included studies [ 55 , 66 68 , 75 86 ] with 574 episodes (Figure 4 ).
Figure 3 Combined resolution rate with 95% CIs of studies of initial treatment with ceftazidime plus a glycopeptide versus a first generation cephalosporin plus an aminoglycoside.
…”
Section: Resultsmentioning
confidence: 99%
“…This resolution rate was significant higher than initial treatment with a first generation cephalosporin plus aminoglycosides (pooled proportion of 66%, 95% CI 0.57–0.75) from 14 included studies [ 57 , 61 , 64 75 ] with 1,438 total episodes (Figure 3 ). Initial treatment with ceftazidime plus a glycopeptide also showed a higher resolution rate than a glycopeptide plus aminoglycosides (pooled proportion of 75%, 95% CI 0.69–0.80) that were used in 16 included studies [ 55 , 66 68 , 75 86 ] with 574 episodes (Figure 4 ).
Figure 3 Combined resolution rate with 95% CIs of studies of initial treatment with ceftazidime plus a glycopeptide versus a first generation cephalosporin plus an aminoglycoside.
…”
Section: Resultsmentioning
confidence: 99%
“…There are also some inconsistencies within the (8). Per Lupo, LD of 400 mg was administered IV; the MD was 40 mg/bag.…”
mentioning
confidence: 99%
“…Some previous clinical studies have demonstrated that empirical therapy with first‐generation cephalosporin and gentamicin has a similar efficacy to regimens using second‐line antibiotics (22,23); however, some studies did not have such favorable results (14,24). In this study the efficacy of an empirical regimen with intermittent intraperitoneal first‐generation cephalosporin and gentamicin was poor.…”
Section: Discussionmentioning
confidence: 57%